ANALISIS MORFOLOGI DAN FILOGENETIK MOLEKULER ALGA HIJAU COCCOID YANG DIISOLASI DARI PULAU ENGGANO - Debora Christin Purbani; Diah Radini Noerdjito; Ismu Purnaningsih; Yeni Yuliani; Danang Ambar Prabowo (BERITA BIOLOGI, 2021)
A combined of morphological characters and molecular approach, is important for evaluating the current classification of microalgae. Phylogenetic trees based on 18S rDNA gene sequence analysis provide useful tools to distinguish between inter- and intra-specific morphologically similar species of coccoid green algae. The aim of the study was to compare the morphological characters and conduct molecular analysis of coccoid green algae isolated from Enggano Island, located southwest of Sumatera, Indonesia. Coccoid green algae samples were collected from different sites at Enggano Island by using a simple random sampling. The single algae were isolated and transferred to IMK medium in flasks by using microcapillaries method. The morphological characteristics of green algae were observed under culture conditions using light microscopy and the phylogenetic positions of the isolated strains were defined according to the 18S rDNA gene sequences. According to homology search (BLAST) and phylogenetic tree analysis, four of the isolated coccoid green algae possessed high sequence similarity, ranging between 90-100%, to Chlorellavulgaris, Auxenochlorella protothecoides, Miractinium reisseri, and Micractinium balenophorum.